O curr??culo de matem??tica da rede estadual de ensino de S??o Paulo - Barbosa, Gabriela (2019)
This essay had as object of study the Paulo State`s curricular proposals of mathematics for the fundamental education II of the Education Secretary. The documents analyzed were the Guias Curriculares para o Ensino do 1?? Grau of 1975; The Proposta Curricular para o Ensino de Matem??tica: 1?? Grau of 1992; and the Curr??culo do Estado de S??o Paulo: Matem??tica e Suas Tecnologias of 2011. The problem that guided our investigation can be presented as: How do the curricular documents look after the discipline of mathematics and its articulation with the other disciplines? The objective of the research was to know how the documents deal with the relation of mathematics with the other disciplines of elementary education II. Our research itinerary involved the analysis of curricular documents produced by the State of S??o Paulo's Education Secretary (SEE / SP). The theoretical references of the research were based on Silva (2010), Apple (2006), Moreira (1989), Sacristan (2000) and Lima (2011). The result of the research shows that the Guias Curriculares (Curriculum Guides) (1975) did not formalize any form of interaction between the disciplines. The Proposta Curricular (Curricular proposal) (1992) endorse the exploration of works that have historical relation and applicability of their contents, maintaining a close relationship with the disciplines of History, Geography and Sciences. The Curr??culo Oficial Paulista (Official Paulista Curriculum) (2011) recognizes the importance of the history of the discipline, defends the partnership of the mother language with the other disciplines and proposes conditions to the Mathematics discipline articulates with all forms of expression.